2001
DOI: 10.1023/a:1011087910699
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Silencing-Mediator for Retinoid/Thyroid hormone receptors (SMRT) interacts with, and mediates transcriptional repression by, a variety of eukaryotic transcription factors, including the nuclear hormone receptors. The ability of SMRT to function as a transcriptional 'corepressor' is regulated by a variety of signal transduction pathways. We report here that SMRT is a phosphoprotein in vivo, and is also phosphorylated in vitro by unfractionated cell extracts. A major site of phosphorylation of SMRT is a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Two other SMRT partners were decreased in the nucleus (Figure 7C ), namely protein kinase CK2 (casein kinase II) and peptidyl-prolyl cis/trans isomerase 1 (Pin1). CK2, which phosphorylates SMRT and has a phospho-acceptor site on HDAC3 [ 50 , 51 ], was reduced markedly in the nucleus 6-24 h post-SFN treatment (lanes 12-14). Pin1, which negatively regulates SMRT protein stability [ 52 ], increased gradually in the nucleus in -SFN controls (lanes 9-11), but remained relatively low in SFN-treated cells (lanes 12-14).…”
Section: Resultsmentioning
confidence: 99%
“…Two other SMRT partners were decreased in the nucleus (Figure 7C ), namely protein kinase CK2 (casein kinase II) and peptidyl-prolyl cis/trans isomerase 1 (Pin1). CK2, which phosphorylates SMRT and has a phospho-acceptor site on HDAC3 [ 50 , 51 ], was reduced markedly in the nucleus 6-24 h post-SFN treatment (lanes 12-14). Pin1, which negatively regulates SMRT protein stability [ 52 ], increased gradually in the nucleus in -SFN controls (lanes 9-11), but remained relatively low in SFN-treated cells (lanes 12-14).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nuclear 24 kDa FGF-2 can interact with the protein kinase CK2 (Bonnet et al, 1996), the ribosomal protein L6/TaxREB107 (Shen et al, 1998b) and with the anti-apoptotic factor FIF (Van den et al, 2000). Several reports have suggested that CK2 is able to control transcription by phosphorylating transcription factors (Grein and Pyerin, 1999;Guo et al, 1999;Zhou et al, 2001). L6/TAXREB107 mediates the DNA binding of the HTLV-1 transactivator Tax (Shen et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, it gets displaced from nuclear receptors by the presence of the cognate hormone, which causes a conformational change in the receptor, creating the ‘ligand-form’ that causes SMRT to dissociate and a CREB Binding Protein/p300-containing coactivator complex to associate [17] . Other signal pathways can also affect interaction of SMRT with transcription factors, for instance, phosphorylation of SMRT by MAPK MEK1 and MEKK1 inhibits interaction of SMRT with nuclear receptors [18] , while SMRT phosphorylation by Casein Kinase II stabilizes the interaction [19] . SMRT stability is also subject to dynamic control.…”
Section: Introductionmentioning
confidence: 99%